Oral hypoglycemic agents in the current treatment of Diabetes Mellitus type 2: Inhibidores de la dipeptidil peptidasa tipo-4 - Arbañil- Huamán, Hugo César (2020)
The concept of incretin effect and its application in the development of drugs that help to control the glycemia in patients with diabetes mellitus type 2 (DM2) is described. Once it was found that this effect was altered in people with diabetes and discovered that this enzyme metabolizes these intestinal hormones, it begin the development of increasingly more specific inhibitors of the enzyme dipeptidil peptidase type-4 /DPP-4). Thereafter the results of cardiovascular safety studies are presented and how these drugs have been positioned in the management guidelines of DM2.